Jogo eletrônico educacional como um objeto de aprendizagem visando a aprendizagem significativa : uma experiência com a análise combinatória - Santos Filho, José Walter (2010)
This research aims to present the experience in developing and implementing an Educational Electronic Game in the form of Learning Objects to Meaningful Learning in order to Combinational Analysis. It analyzes the potential of this way of teaching applied in the classroom. This activity was implemented in a public school in Aracaju, with 19 students in 2nd year of high school. When analyzing the Learning Objects since its construction as Educational Electronic Game, their implementation and achievement of results, looking for evidence if this game is shaped as a cognitive tool aimed at meaningful learning according to the theory of David P. Ausubel (1968, 2003). In constructing the game was perceived a variety of forms of education Combinatorial Analysis using the strategy of solving problem situations, presentation of formulas and stimulating the development of logical thinking, which was integrated into the Learning Objects. Were defined learning objectives from Bloom's Taxonomy (1973), that the gains are achieved provided to students in their cognitive domain. Anchored in the Theory of Meaningful Learning of Ausubel, Educational Electronic Game was constructed and applied by this researcher with a specialist teacher in mathematics. The device uses concept maps and interactive animations in the form of Electronic Gaming Education to support the mediation, and can be regarded as Learning Objects to be an Educational Software that weaves the recreational and educational functions in the form of game.The survey found its end that students have built new mathematical knowledge by recalling the concepts, understand the significance of multiplicative principle, implement, analyze and evaluate the logical thinking and create problems Combinatorial Analysis. Configures itself so this Educational Electronic Game in the form of Learning Objects as an organizer of prior knowledge, working as cognitive support in order to Meaningful Learning.